P243 Anti-rituximab antibodies demonstrate neutralising capacity, associate with lower circulating drug levels and early relapse in patients undergoing treatment for systemic lupus erythematosus. (23rd April 2022) - Wincup, Chris; Dunn, Nicky; Ruetsch-Chelli, Caroline; Manouchehrinia, Ali; Kharlamova, Nastya; Naja, Meena; Seitz-Polski, Barbara; Isenberg, David; Fogdell-Hahn, Anna; Ciurtin, Coziana; Jury, Elizabeth
Abstract: Background/Aims: A major limitation of biologic therapy is formation of anti-drug antibodies (ADA). We previously demonstrated that ADA to rituximab are more prevalent in patients undergoing treatment for systemic lupus erythematosus (SLE) than rheumatoid arthritis and vasculitis, and predict subsequent infusion reactions. However, little is known regarding the long-term dynamics of ADA to rituximab. In this study we evaluated the longitudinal impact of ADA positivity in terms of drug kinetics, treatment response and neutralising capacity in SLE. Methods: Patients with SLE undergoing treatment with rituximab were recruited to this study (n = 35). Serum samples were collected at the following intervals post-treatment; 1-3 months, 6 months, 12 months, 36 months (n = 114). Clinical and laboratory data was collected pre-treatment and at each time point. ADA were detected using an electrochemiluminescent immunoassay. Serum rituximab levels were measured via ELISA. A complement dependent cytotoxic assay was used to determine neutralising capability of ADA in a subgroup of positive samples (n = 38). Results: ADA were found to be persistently positive over the 36-month follow-up period in 64.3% of patients. There was no significant difference in baseline disease activity (BILAG / SLEDAI-2K) between those who were subsequently ADA positive vs negative. ADA positive patients were younger at diagnosis compared with ADA negative (mean 22.50 ± 9.10 vs 37.29 ± 11.31 years, p = 0.002). Multivariate logistic regression found older age at diagnosis was associated with reduced incidence of persistent ADA with a 22% decrease in risk for each addition year after diagnosis (p = 0.03). ADA positive patients had a significantly lower C3 level at baseline (mean 0.61 ± 0.23 vs 0.87 ± 0.30, p = 0.026), which remained lower at each subsequent time point post-treatment up to 12 months. ADA titres peaked earlier and remained higher in those who had been treated with rituximab previously compared with those who were rituximab naive (median 132 AU/ml vs 7 AU/ml at 1-3 months). At 6 months post-treatment, patients with detectable ADA had a significantly lower circulating drug level than ADA negative (p = 0.0018). In terms of clinical response, ADA positive patients had an initial significant improvement in disease activity (SLEDAI-2K) by 3 months (p < 0.001). However, response was not maintained at 12 months. In comparison, ADA-negative patients showed a significant improvement in SLEDAI-2K at 6 months and this was maintained across the 36-month follow-up period. BILAG defined relapse within 12 months of treatment was only seen in ADA positive patients. Finally, all ADA positive samples were found to neutralise rituximab in vitro. Conclusion: ADA to rituximab were common and persisted over the 36 month period of this study. ADA associated with earlier drug elimination, increased relapse rates and demonstrated neutralising capacity suggesting that ADA could be a significant limitation to sustained response to treatment. Disclosure: C. Wincup: Grants/research support; Lupus UK, Versus Arthritis, British Society for Rheumatology. N. Dunn: None. C. Ruetsch-Chelli: None. A. Manouchehrinia: None. N. Kharlamova: None. M. Naja: None. B. Seitz-Polski: None. D. Isenberg: None. A. Fogdell-Hahn: None. C. Ciurtin: None. E. Jury: None.